2015
DOI: 10.1186/s13705-014-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Foam formation in full-scale biogas plants processing biogenic waste

Abstract: Background: The proportion of biogas in the mix of renewable energies is still remarkably high. The process of anaerobic digestion (AD) provides the basis of biogas production but often leads to excessive foaming. Identifying the reasons for foaming is difficult for biogas plant operators because many factors may play a role. It is therefore difficult for laboratory research to give answers to this specific problem, as the consistency of the digestate itself plays a crucial part in the foam formation process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
(68 reference statements)
1
25
1
Order By: Relevance
“…Bulking of the sludge may cause severe damage to biogas installations (Lindorfer and Demmig 2016). Such shifts in viscosity of the reactor sludge may result in problems with foaming and inadequate mixing, ultimately leading to breakdown of stirrers (Nordberg and Ekström 2005;Björn et al 2012;Kougias et al 2014;Moeller et al 2012;Moeller and Görsch 2015). Previous research on the rheology, including viscosity, of anaerobic digester sludge has mainly focused on plants digesting sewage sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Bulking of the sludge may cause severe damage to biogas installations (Lindorfer and Demmig 2016). Such shifts in viscosity of the reactor sludge may result in problems with foaming and inadequate mixing, ultimately leading to breakdown of stirrers (Nordberg and Ekström 2005;Björn et al 2012;Kougias et al 2014;Moeller et al 2012;Moeller and Görsch 2015). Previous research on the rheology, including viscosity, of anaerobic digester sludge has mainly focused on plants digesting sewage sludge.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of them could be used for the prediction of foam formation. Previous research has shown that the formation of foam in AD is the result of a disorder in the hydrolysis stage of the AD of organic material [2,9]. For this reason, none of the commonly measured parameters are suitable as EWIs for foaming because only analytes connected with the later stages of biogas production such as volatile fatty acids are observed in practice.…”
Section: Process Upset Indicatorsmentioning
confidence: 99%
“…Furthermore, the use of some substrates such as grain [9], sugar beet [10][11][12], or yeast [2] can even in relatively small amounts lead to foam formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, it was reported that the usage of commercial antifoams did not have any successful effect on combating foaming in a mesophilic two-stage biogas plant in Germany (Moeller and G€ orsch, 2015). One important parameter defining the suitability of the chemicals to be used as antifoaming agents, especially for biological process, is their toxicity.…”
Section: Introductionmentioning
confidence: 99%